A tablet-based intervention study to alleviate cognitive and psychological symptoms in patients with post-Covid-19 condition - Leitner, Manuel; Paletta, Lucas; Leal-Garcia, Manuel; Fellner, Maria; Koini, Marisa (Frontiers in Psychology, 2025)
BackgroundCognitive impairment and psychological complaints are among the most common consequences for patients suffering from Post-Covid-19 condition (PCC). As there are limited training options available, this study examined a longitudinal tablet-based training program addressing cognitive and psychological symptoms.MethodsForty individuals aged between 36 and 71 years (M = 49.85, SD = 8.63; 80% female) were randomly assigned to either an intervention group (n = 20) or a waitlist control group (n = 20). The intervention group received a three-month tablet-based training program involving cognitive exercises, relaxation techniques, and physiotherapy exercises. Additionally, both groups underwent a thorough neuropsychological assessment (attention, memory, executive functions, word fluency, subjective cognitive complaints, fatigue, depression, anxiety, and quality of life) before the training, after 3 months of training, and after 6 months in order to assess long-term effects.ResultsPre-post comparisons revealed that individuals assigned to the intervention group (n = 18 after dropout), as compared to the control group (n = 16 after dropout), showed a reduction in subjective cognitive complaints (p < 0.001) as well as in depressive symptoms (p < 0.001). Additionally, their MoCA Memory Index Score remained stable (p = 0.496), while it declined significantly in the wait-list control group (p = 0.008). However, the training had no effect on the other domains assessed and not all training-related effects were stable over time. Finally, a higher number of post-Covid symptoms was negatively correlated with attention and memory capabilities (all p < 0.05), with a longer disease duration further amplifying the negative impact of post-Covid symptoms on memory performance.ConclusionTablet-based training programs can help improve subjective complaints, depressive symptoms, and memory and may serve as an additional therapy option. Further studies are needed to investigate the stability of these effects.